2016
DOI: 10.1002/mrc.4400
|View full text |Cite
|
Sign up to set email alerts
|

Di(ethylene glycol) methyl ether methacrylate (DEGMEMA)‐derived gels align small organic molecules in methanol

Abstract: Residual dipolar couplings (RDCs) constitute an important NMR parameter for structural elucidation in all areas of chemistry. In this study, di(ethylene glycol) methyl ether methacrylate (DEGMEMA)-based gels are introduced as alignment media for the measurement of RDCs of small organic molecules in polar solvents such as methanol. The low viscosity of methanol permits the execution of J-scaled BIRD HSQC experiments that yield very sharp lines in anisotropic conditions. The gels have excellent mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…3a, b ). Using only 1 D CH RDCs it was not possible to assign the correct configuration of retrorsine 41 mainly due to lack of information about the quaternary chiral center at C11. However, the configuration analysis of retrorsine was accomplished using 13 C RCSAs 20 .…”
Section: Resultsmentioning
confidence: 99%
“…3a, b ). Using only 1 D CH RDCs it was not possible to assign the correct configuration of retrorsine 41 mainly due to lack of information about the quaternary chiral center at C11. However, the configuration analysis of retrorsine was accomplished using 13 C RCSAs 20 .…”
Section: Resultsmentioning
confidence: 99%
“…As a fourth example, we chose the alkaloid retrorsine, a compound examined in a number of earlier NMR studies, Figure 6. 48 It is noteworthy that a previous attempt at RDC-based configuration assignment was unsuccessful. 48 Using the stretching device, we collected 16 ΔRCSAs to test whether ΔRCSAs could assign the correct configuration in contrast to the RDC results.…”
Section: ■ Methods Sectionmentioning
confidence: 99%
“…48 It is noteworthy that a previous attempt of RDC-based configuration 19 assignment was unsuccessful. 48 Using the stretching device, we collected sixteen RCSAs to test whether RCSAs could assign the correct configuration in contrast to the RDC results.…”
Section: (D) Retrorsinementioning
confidence: 99%
“…If this is not the case, either by the presence of paramagnetic metal ions [24] or anisotropic susceptibility of diamagnetic macromolecules [25] or, more general, the presence of an anisotropic medium, the molecules will be partially oriented with respect to the external magnetic field, and residual dipolar couplings (RDCs) can be measured (detailed reviews can be found at [26][27][28][29][30][31]). An anisotropic environment is generated by an alignment medium (AM), examples for AMs are stretched gels [32][33][34][35][36][37][38][39][40] or lyotropic liquid crystalline (LLC) phases [41][42][43][44][45][46][47][48][49].…”
Section: Rdcs In Structure Elucidationmentioning
confidence: 99%